Logistics network optimization considering balanced allocation and vehicle routing - Cho, Su Yeon; Lee, Young Hae; Cho, Dong Won; Gen, Mitsuo (Maritime economics & logistics, 2016)
This article presents an effort to study the complex problem that arises when balanced allocation is integrated with vehicle routing decisions in a logistics network. This integrated problem is frequently encountered in many logistics networks that maximize the efficiency and effectiveness of available warehouses and distribution centers. After modeling the balanced allocation vehicle routing problem (BAVRP) as a multi-objective mixed integer programming problem, we propose a two-stage approach as a solution methodology. This approach decomposes the BAVRP into two independent sub-problems, allocation and routing, and solves them separately. Experimental results show that our two-stage algorithm approach is readily applicable to the BAVRP.